The impact of foreign equity investment flows on integration of Asian emerging equity markets - Poshakwale, Sunil S.; Thapa, Chandra (Cranfield University School of Management, 2009)
The paper investigates the impact of foreign equity investment flows on the integration process of emerging markets with the global markets. Daily net foreign equity investment flow and return data for the four Asian emerging markets of India, Korea, Taiwan, and Thailand for 2001-2007 is used in examining the long and short-run relationship with the global markets. The findings show that despite the instability of the correlation structure, there is a general trend towards greater integration. The cointegration analysis results suggest that the four Asian emerging markets are getting integrated with the global markets and the integration process is driven by the activities of the foreign investors. Findings confirm that the global markets have significant causal impact on returns of all four emerging markets and the foreign equity investment flows play a significant role in correcting the short-term deviations in the convergence process. Whilst the results are consistent with previous research, we find stronger evidence for the positive feedback hypothesis for all four markets. The results support the widely held view that foreign investors are high return chasers and extract information from recent returns. Our results also confirm the price pressure hypothesis which suggests that foreign equity investors are mainly responsible for the increase in the stock market valuations in the four Asian emerging markets. If this were to be true, the emerging markets may become increasingly vulnerable to the shocks in the volume of foreign equity investment flows and turn more volatile in future.
Keywords: Foreign equity investors; Asian emerging markets; Cointegration and VEC; Global linkages and short-run dynamics